The poetic nature of the works on the theme of the Afghan war - Kulbarak С.О.; Tuyakbayev Ғ.Ә.; Utkelbaev Қ.З. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2021)
The regularity of art is the artistic and historical depiction of important events in the history of mankind in literature and fiction, and the creation of images of individual heroes. One such event in the history of the USSR was the 10-year war in Afghanistan (1979-1989). The giant empireinvaded the territory of Afghanistan and conducted military operations in 21 provinces of the country. Conscripts from Kazakhstan also took part in these battles. The battalion of 27-year-old Bakytzhan Yertayev conducted a brave battle on the banks of the Kunar River, and the battalion of Boris Kerimbayev, known as the “black major”, conducted a brave battle in the valley “Pansher”. The war was not without losses. In peacetime, many marriages have suffered. 22 thousand people from Kazakhstan took part in the war, about 1000 of them were victims of the war, 20 people went missing [1]. Heroism and tragedy leave their mark on life and art. News of the war in Afghanistan was not made public. The beginning of the truth was connected with the end of the war and the safe return of the participants of the war. Initially, memoirs, articles and interviews of various kinds, essays, dedication poems, war lyrics were written. The book “Bozdaktar” (about heroes) has been published. As the memories grew, so did the art of journalism. Kazakh writers began to write regularly on Afghanistan. Books in various genres began to appear. The fate of a man who fought in the Afghan war has become a character of fiction as a difficult and twisted image. At least, there is a literary and journalistic process in the literature and journalism on the subject of the Afghan war. This war played a special role in the development of national military prose and other genres of military literature. After all, the situation of the war experienced by the generation and the suffering it brought to the country is a law of life and art, which presents its theme in literature and fiction. The writing of works of various genres is a topical issue in the history of literature